Ergonomics-Aware Scheduling: Biomechanical Models with Production Planning Integration for Musculoskeletal Risk Reduction - Chukwumuanya Emmanuel Okechukwu; Okpala Charles Chikwendu; Onukwuli Somto Kenneth (Journal Majelis Paspama, 2025)
Work-related Musculoskeletal Disorders (MSDs) remain a significant challenge in industrial environments, as they contribute to lost productivity, high compensation costs, and reduced workforce well-being. Traditional production scheduling practices often prioritize throughput and efficiency, overlooking ergonomic considerations. This study proposes an ergonomics-aware scheduling framework that integrates biomechanical modeling with production planning to reduce MSD risks while sustaining operational performance. Using case studies in an assembly line, a machining workshop, and a packaging section, the framework applied biomechanical risk models to inform scheduling algorithms. The results showed substantial reductions in both peak and cumulative physical loads which are 23% and 19% in assembly, 28% and 21% in machining, and 31% and 26% in packaging, while maintaining productivity with minimal trade-offs. Qualitative benefits included improved inclusivity, greater adaptability to demand fluctuations, and enhanced worker-task matching. The discussion highlights the implications for industry, and emphasize how ergonomics-aware scheduling supports sustainable productivity, lowers injury risks, and also aligns with Industry 4.0 through real-time monitoring and digital twins. The limitations include simplified biomechanical models, limited case study scope, and data requirements. Future research should explore machine learning integration, broader validation across sectors, and longitudinal studies on long-term organizational outcomes. Overall, ergonomics-aware scheduling provides a promising pathway towards the designing of production systems that are not only efficient, but also safe, inclusive, and sustainable.